2020
DOI: 10.1038/s41598-019-57383-x
|View full text |Cite
|
Sign up to set email alerts
|

A CBL-interacting protein kinase AdCIPK5 confers salt and osmotic stress tolerance in transgenic tobacco

Abstract: cBL interacting protein kinases play important roles in adaptation to stress conditions. in the present study, we isolated a CBL-interacting protein kinase homolog (AdCIPK5) from a wild peanut (Arachis diogoi) with similarity to AtCIPK5 of Arabidopsis. Expression analyses in leaves of the wild peanut showed AdCIPK5 induction by exogenous signaling molecules including salicylic acid, abscisic acid and ethylene or abiotic stress factors like salt, PEG and sorbitol. The recombinant AdCIPK5-GFP protein was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Of those, a CBL‐interacting protein kinase and S‐Phase Kinase‐Associated Protein 2A (SKP2A) were also implicated in local adaptation in lodgepole pine ( Pinus contorta ) and interior spruce (Yeaman et al., 2016). The CBL‐interacting protein kinase family has also been found to be involved in response to stresses in angiosperms (Singh et al., 2020), while SKP2A is an auxin‐binding protein that connects auxin signaling and cell division (Jurado et al., 2010). These annotations are indicative of potentially important adaptive roles which appear to be largely shared across plants.…”
Section: Resultsmentioning
confidence: 99%
“…Of those, a CBL‐interacting protein kinase and S‐Phase Kinase‐Associated Protein 2A (SKP2A) were also implicated in local adaptation in lodgepole pine ( Pinus contorta ) and interior spruce (Yeaman et al., 2016). The CBL‐interacting protein kinase family has also been found to be involved in response to stresses in angiosperms (Singh et al., 2020), while SKP2A is an auxin‐binding protein that connects auxin signaling and cell division (Jurado et al., 2010). These annotations are indicative of potentially important adaptive roles which appear to be largely shared across plants.…”
Section: Resultsmentioning
confidence: 99%
“…The evolution of stress-related genes is a crucial part of the adaptation process. Notably, we observed that selection sweeps (harboring stress-related genes) overlapped with each other in the different comparisons, suggesting that a subset of genomic regions were selected during domestication and may have undergone successive selections, such as genes encoding hypersensitivity-related protein (HSR) (Lacomme and Roby, 1999), cellulose synthase (CeS) (Burn et al, 2002), plant disease resistance proteins (Martin et al, 2003), ABC transporters (ABCTs) (Martinoia et al, 2002), cytochrome P450 (CYP450) (Field and Osbourn, 2008), callose synthase (CaS) (Shi et al, 2016), CBL-interacting protein kinase (CIPK) (Singh et al, 2020), and a-farnesene synthase (AFS) (Jin et al, 2020;Wang et al, 2019) (Table S28). In addition, for the transcription factors involved in the development processes, disease resistance, and hormone-related functions (e.g., indole-3butyric acid, abscisic acid, and ethylene), the nucleotide diversities of the F and NE groups were significantly higher (Figure S18a; Table S28).…”
Section: Selection Sweep During Migration Hybridization and Domesticationmentioning
confidence: 99%
“…NtPPO is a polyphenol oxidase gene involved in stress tolerance in many plants [ 52 ]. NtNECD1 plays an important role in ABA biosynthesis [ 53 ]. NtP5CS encodes a key enzyme in proline biosynthesis [ 54 ].…”
Section: Discussionmentioning
confidence: 99%